A pH/ROS-responsive, tumor-targeted drug delivery system based on carboxymethyl chitin gated hollow mesoporous silica nanoparticles for anti-tumor chemotherapy. (1st October 2020) - Ding, Xiao; Yu, Wenjie; Wan, Yunfeng; Yang, Mingyue; Hua, Chenghuan; Peng, Na; Liu, Yi
Highlights: A nanosystem based on CMCH gated HMSNs with pH/ROS-responsive and tumor-targeting characteristics was fabricated. The nanosystem exhibited good biocompatibility and elevated anti-tumor efficacy. The nanosystem showed great potential as a novel carrier for chemotherapy. Abstract: A new nanosystem was prepared by coating ROS-cleavable thioketal (TK) bonded hollow mesoporous silica nanoparticles with carboxymethyl chitin via electrostatic interaction and further surface-anchored with glucose-regulated protein 78 binding peptide for targeted-delivery of doxorubicin (DOX) and α-tocopheryl succinate (α-TOS). The nanosystem (HMSN-TK-CMCH-GRP78P) showed an average size of 265 nm after loading DOX and α-TOS with a drug loading content of 4.06 % and 7.64 %, respectively. The in vitro release studies revealed the pH/ROS dual-responsibility of DOX/α-TOS loaded HMSN-TK-CMCH-GRP78P. The released α-TOS increased the intracellular ROS concentration, which could induce the cleavage of TK linkages and in turn accelerate DOX release. Moreover, the nanosystem could target to 4T1 cells, causing cell death in vitro and suppress tumor growth in vivo in 4T1-bearing BALB/c mice with reduced side effects, which illustrated that the nanosystem led to an effective anti-tumor efficacy and exhibited as a promising carrier to deliver chemotherapeutic agents for chemotherapy.